PELATIHAN HYDROPONIK MENGGUNAKAN MEDIA BARANG BEKAS SOLUSI MENGURANGI LIMBAH SAMPAH DI DESA PILANGSARI - Evi Masliyatu Rofiqoh Evi; Asep Kamaludin; Ibnu Rusdi; Fitri Nirma; Nuniek Rahmatika (Al Naqdu, 2023)
One of the problems in Pilangsari Village is environmental problems such as the presence of plastic waste and limited land in the community. From this problem, we provide training in Hydroponics as a planting medium that does not require a large area of ​​land, and the tools and materials needed can be utilized from waste waste. In addition, the opportunity to plant with hydroponic media is more efficient than other planting media because it does not require a large area because what must be considered in this planting medium is only providing nutrients, circulating water, and occasionally caring for the planting media by cleaning. In order to maximize this, we are planting using Hydroponic planting media so that in the future Pilangsari Village becomes an example of Hydroponic planting for the surrounding community.